Enhancing the vaporization and secondary atomization of two-liquid droplets for fire suppression; Fire Safety Journal; Vol. 146 - Antonov D. V. Dmitry Vladimirovich; Kovalev D. N. Dmitry Nikolaevich; Shakhray M. S. Mikhail Sergeevich; Fedorenko R. M. Roman Mikhaylovich (2024, 2024)
Title screen